2003
DOI: 10.1051/rnd:2003003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal environment on the number of transferable embryos obtained in response to superovulatory FSH treatments in ewes

Abstract: -In a first experiment, embryo viability was estimated after recovery in the uterus or the oviduct of 70 Manchega ewes following a treatment of superovulation with decreasing doses of OVAGEN TM . Fewer viable embryos (5.6 ± 0.9 vs. 8.3 ± 0.8, P < 0.05) and more degenerative embryos (31.3% vs. 6.8%, P < 0.005) were obtained from the uterus than from the oviduct respectively. In a second experiment performed on 14 ewes, embryo viability was analyzed in relation to the follicular population estimated by ultrasono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 38 publications
1
13
0
2
Order By: Relevance
“…This occurs in approximately 20-30% of the ewes (GONZALEZ-BULNES et al, 2000). A possible cause may a deficient or inexistent preovulatory LH surge (GONZALEZ-BULNES et al, 2003) or the presence of non-responsive follicles due to a downregulation of the granulosa and theca LH receptors (LOPEZ-DIAZ & BOSU, 1992). COGNIÉ et al (1986) suggested that the administration of LH at the end of SOV treatment with exogenous FSH might increase the ovulation rate and the number of recovered embryos.…”
Section: Sincroniza O Tempo Das Ovulações E Incrementa a Taxa De Ovulmentioning
confidence: 99%
“…This occurs in approximately 20-30% of the ewes (GONZALEZ-BULNES et al, 2000). A possible cause may a deficient or inexistent preovulatory LH surge (GONZALEZ-BULNES et al, 2003) or the presence of non-responsive follicles due to a downregulation of the granulosa and theca LH receptors (LOPEZ-DIAZ & BOSU, 1992). COGNIÉ et al (1986) suggested that the administration of LH at the end of SOV treatment with exogenous FSH might increase the ovulation rate and the number of recovered embryos.…”
Section: Sincroniza O Tempo Das Ovulações E Incrementa a Taxa De Ovulmentioning
confidence: 99%
“…The concentration of peripheral oestradiol was measured using the Spectria RIA kit (Orion Diagnostic Corp., Espoo, Finland), as described by Romeu et al (1995) and adapted for use in ovine plasma (Gonzalez-Bulnes et al 2003). Sensitivity for oestradiol was 5 pmol/l and the inter-and intra-assay variation coefficients were 17.6 and 18.1% respectively.…”
Section: Determination Of Glucose and Hormones (Ghrelin Oestradiol Amentioning
confidence: 99%
“…Cross-reactivity with IGF-II, insulin and proinsulin was negligible. Estradiol concentrations were measured in one single assay using the Spectria radioimmunoassay kit (Orion Diagnostic Corp., Espoo, Finland), as described by Romeu et al (1995) and adapted for use in ovine plasma (Gonzalez-Bulnes et al, 2003). Sensitivity for estradiol was 0.5 pg/ml and the intra-assay variation coefficient was 6.6%.…”
Section: Igf-i and Estradiol Immunoassaysmentioning
confidence: 99%